Membrane ion Channels and Receptors in Animal lifespan Modulation. Issue 11 (3rd February 2017) - Sheng, Yi; Tang, Lanlan; Kang, Lijun; Xiao, Rui
Abstract : Acting in the interfaces between environment and membrane compartments, membrane ion channels, and receptors transduce various physical and chemical cues into downstream signaling events. Not surprisingly, these membrane proteins play essential roles in a wide range of cellular processes such as sensory perception, synaptic transmission, cellular growth and development, fate determination, and apoptosis. However, except insulin and insulin‐like growth factor receptors, the functions of membrane receptors in animal lifespan modulation have not been well appreciated. On the other hand, although ion channels are popular therapeutic targets for many age‐related diseases, their potential roles in aging itself are largely neglected. In this review, we will discuss our current understanding of the conserved functions and mechanisms of membrane ion channels and receptors in the modulation of lifespan across multiple species including Caenorhabditis elegans, Drosophila, mouse, and human. Abstract : Acting in the interfaces between environment and membrane compartments, membrane ion channels and receptors transduce various physical and chemical cues into downstream signaling events. In this review, we will discuss our current understanding of the conserved functions and mechanisms of membrane ion channels, and receptors in the modulation of lifespan across multiple species including Caenorhabditis elegans, Drosophila, mouse, and human.